Ensino de botânica e meio ambiente: um guia didático para aulas em espaços não formais amazônicos - Vilas Boas, Terezinha de Jesus Reis (Brasil, 2019)
In this respect, it is recognized that education for science is not only a function of the school, but its role in educating the relevance in teaching-learning. Non-formal spaces (ENFs) appear as environments used for dissemination of local specificities necessary for scientific and environmental training. Thus, it was tried to construct this Didactic Guide organized in forest environments of the Amazon Region around questions about: The importance of the vegetables to the Amazonian environment for the acquisition of a consistent environmental conception in its practice. In this guide we highlight the importance of the regional flora for botanical studies in a perspective of building associated botanical knowledge environmental issues with the use of the following spaces: Biological Reserve of Campina / Campinarana, Suframa Waterfall, Cachoeira Santa Cláudia, Municipal Park Cachoeira das Orquídeas. Through this Pedagogical Guide there are information on how a teacher can use these spaces to highlight the richness of natural resources in the Amazon, carrying out teaching-learning processes with regional examples, valuing and allowing the individual to understand the importance of living beings for the maintenance of the environment. The approach also allows the correlation between the knowledge described during a theoretical class and the examples shown in the textbooks.